PHYTOCHEMICAL SCREENING, ANTIMICROBIAL, AND ANTIOXIDANT ANALYSIS OF BERBERIS LYCIUM ROYLE CRUDE ROOT EXTRACTS - SANGRAL, MONICA; GUPTA, DIVYA; SINGH, PARAMVEER; LOCHAN, ROSHANI; BHAT, NAZLI; KIRANBALA; BHAGAT, MADHULIKA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This particular study was designed to evaluate the qualitative, quantitative, anti-oxidant, and antimicrobial potential of Berberis lycium root extracts. Methods: The plant root extracts were prepared using a sequential extraction method using different solvents with increasing polarity. Further extracts were evaluated qualitatively for the presence of different phytochemicals and quantitatively for the presence of total phenols and flavonoid, antioxidant potential using DPPH, ferric reducing anti-oxidant power, and H2O2 radical scavenging assay. Biological potential of these extracts was established for antibacterial effect against different Gram-negative and Gram-positive bacteria and antifungal potential against fungal strains. Results: Qualitative analysis of the root extracts showed the presence of phytochemicals such as saponins, tannins, phenols, and flavonoids. Among all the evaluated extracts in quantitative analysis, methanolic extracts showed the highest content of phenolic with 39.75 mg gallic acid equivalence/g and flavanoid with 456 mg QE/g, highest antioxidant potential with half-maximal inhibitory concentration (IC50) value of 10.96 μg/mL in DPPH assay. Similarly, the highest antibacterial effect against Bacillus cereus (20±0.86 mm) and antifungal against Aspergillus niger (IC50 399.64 μg/mL) was observed. Conclusion: The plant root extracts of B. lycium have shown substantial content of phytochemicals with appreciable antioxidant and antimicrobial activities comparable to the currently prescribed modern drugs tested. Accordingly, further studies on clinical efficacy trial, safety, and toxicity analyses have to be instigated promptly, so as to head to the final step to synthesize precursor molecules for new effective antimicrobials.